Cerebrospinal Fluid Cell-Free DNA-Based Detection of High Level of Genomic Instability Is Associated With Poor Prognosis in NSCLC Patients With Leptomeningeal Metastases - Wu, Xi; Xing, Puyuan; Shi, Min; Guo, Weihua; Zhao, Fangping; Zhu, Honglin; Xiao, Jianping; Wan, Jinghai; Li, Junling (Frontiers in Oncology, 2022)
Introduction Leptomeningeal metastasis (LM) commonly occurs in non-small cell lung cancer (NSCLC) patients and has a poor prognosis. Due to limited access to leptomeningeal lesions, the genetic characteristics of LM have not been explored to date. Cerebrospinal fluid (CSF) may be the most representative liquid biopsy medium to obtain genomic information from LM in NSCLC. Methods CSF biopsies and matched peripheral blood biopsies were collected from 33 NSCLC patients with LM. We profiled genetic alterations from LM by comparing CSF cell-free DNA (cfDNA) with plasma cfDNA. Somatic mutations were examined using targeted sequencing. Genomic instability was analyzed by low-coverage whole-genome sequencing (WGS). Results Driver mutations were detected in 100% of CSF cfDNA with much higher variant allele frequency than that in matched plasma cfDNA (57.5%). Furthermore, we found that the proportions of CSF cfDNA fragments below 150 bp were significantly higher than those in plasma cfDNA. These findings indicate enrichment of circulating tumor DNA (ctDNA) in CSF and explain the high sensitivity of mutation detection in the CSF. The absence of some mutations in CSF cfDNA—especially the first-/second-generation mutation T790M, which confers resistance to epidermal growth factor receptor (EGFR)-Tyrosine kinase inhibitors (TKIs)—that were present in plasma cfDNA samples indicates different mechanisms of cancer evolution between LM and extracranial lesions. In addition, 86.6% of CSF ctDNA samples revealed high levels of genomic instability compared with 2.5% in plasma cfDNA samples. A higher number of large-scale state transitions (LSTs) in CSF cfDNA were associated with a shorter overall survival (OS). Conclusion Our results suggest that LM and extracranial lesions develop independently. Both CSF cfDNA genetic profiling and plasma cfDNA genetic profiling are necessary for clinical decision-making for NSCLC patients with LM. Through CSF-based low-coverage WGS, a high level of LSTs was identified as a potential biomarker of poor prognosis.